Attention regulation in women with ADHD and women with bipolar disorder: An ex-Gaussian approach. (March 2020) - Vainieri, Isabella; Adamo, Nicoletta; Michelini, Giorgia; Kitsune, Viryanaga; Asherson, Philip; Kuntsi, Jonna
Highlights: ADHD and BD shared a cognitive impairment observed as infrequent slow responses (tau) in the slow, unrewarded condition of the fast task. A BD-specific impairment emerged in the variability of typical RT responses (sigma), on the incongruent condition of the arrow flanker task. These shared and BD-specific impairments represent potential cognitive markers that should be further investigated in future studies with both men and women with the disorders. Abstract: Attention-deficit/hyperactivity disorder (ADHD) and bipolar disorder (BD) show certain overlapping features, such as increased reaction time variability. Here, we tested whether more detailed ex-Gaussian reaction time distribution measures identify shared or disorder-specific impairments in ADHD and BD. The total assessed sample consisted of 60 women (20 each in ADHD, BD and control groups). We compared the groups on ex-Gaussian measures of mu, sigma, and tau from a flanker task (congruent and incongruent conditions), an oddball task, and a four-choice reaction time task (baseline and fast-incentive conditions of the `fast task'). The ex-Gaussian measures mu and sigma reflect the speed and variability of typical responses, while tau captures variability in infrequent slow responses. Compared to controls, both ADHD and BD groups showed significantly increased tau in the fast task baseline condition. Participants with BD further showed a significantly increased sigma compared to ADHD and control groups in the flanker task incongruent condition. Our findings indicate that the ex-Gaussian approach is informative in detecting shared and disorder-specific cognitive impairments in ADHD and BD that may represent objective markers of these two disorders.